1998
DOI: 10.1164/ajrccm.157.3.97-05009
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Nitric Oxide in Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by progressive airflow obstruction and a neutrophilic inflammation. Exhaled nitric oxide (NO) may be a marker of disease activity in a variety of lung diseases. We measured exhaled NO in patients with documented COPD and investigated whether the concentration of exhaled NO is related to the severity of disease as defined by lung function. We also investigated whether concentration of exhaled NO was different in COPD patients who received inhaled ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
172
7
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(211 citation statements)
references
References 28 publications
(26 reference statements)
25
172
7
5
Order By: Relevance
“…Another hypothesis relates smoking-induced pulmonary changes due to COPD as the cause of decreased FeNO in smokers. As stated earlier, while most studies found that FeNO levels increase in patients with COPD [4,45], more recent data from ROY et al [44], using multiple measurements of exhaled NO at different flow rates to model airway NO, suggests that FeNO levels are lower in COPD patients. Like the hypothesis about smokingrelated respiratory epithelial damage, the COPD hypothesis would associate COPD-related inflammatory changes and parenchymal lung damage with reductions in FeNO.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Another hypothesis relates smoking-induced pulmonary changes due to COPD as the cause of decreased FeNO in smokers. As stated earlier, while most studies found that FeNO levels increase in patients with COPD [4,45], more recent data from ROY et al [44], using multiple measurements of exhaled NO at different flow rates to model airway NO, suggests that FeNO levels are lower in COPD patients. Like the hypothesis about smokingrelated respiratory epithelial damage, the COPD hypothesis would associate COPD-related inflammatory changes and parenchymal lung damage with reductions in FeNO.…”
Section: Discussionmentioning
confidence: 88%
“…Although ROY et al [44] recently found that COPD was associated with decreased airway NO levels, most studies suggest that COPD is associated with increased FeNO levels [4,45] and, if anything, this would have diminished the difference in FeNO levels between older smokers and nonsmokers. Taken together, the current authors believe that long-term smoking may result in permanent reductions in FeNO levels, possibly via airway epithelial lining changes and changes in NOS2 expression and NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators [24,25] demonstrated that smoking could reduce endogenous NO production. In this study, there were no significant differences in NO metabolite level in the induced sputum between smokers and nonsmokers in asthmatic subjects as well as in normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Increased exhaled NO levels were observed in ex-smokers with COPD compared to healthy non-smokers, and in current smokers with COPD compared to healthy current smokers (Corradi et al, 1999;Montuschi et al, 2001). Moreover, exhaled NO is increased during COPD exacerbations compared with stable COPD (Maziak et al, 1998). In addition, RNS such as nitrotyrosine and nitrothiol can cause damage to the lung.…”
Section: Ros Rns and Nomentioning
confidence: 96%